Collection and Storage of Solar Gains Incident on the Floor in a House During the Heating Season. (November 2015) - Brideau, Sébastien; Beausoleil-Morrison, Ian; Kummert, Michaël
Abstract: Large amounts of south facing windows can help reduce heating demand in the winter and shoulder seasons by allowing high levels of solar radiation to enter the building. One problem that may arise from large areas of south facing glazing is overheating of the adjacent rooms, even during winter in a cold climate. Cooling of the floors may provide a means to prevent overheating in such a situation. Cooling a floor prevents solar gains absorbed by the floor from being transferred to the space by convection or infrared radiation. This cooling can be achieved with the use of water pipes in the floor. The heat removed can be upgraded to a higher temperature with a heat pump, and then may be stored in a thermal storage tank for space heating and domestic hot water heating. This paper shows preliminary simulation results of such a system for a house in Ottawa, Canada. The house contains a much larger south facing window area than is typical. In periods of overheating, the solar gains are absorbed by the floor cover and collected by the cold pipes in the floor. The heat is upgraded by a heat pump and stored in a hot storage tank. Preliminary modelling results show that, with the use of a large thermal storage tank (2 m3), space heating and domestic hot water demand with this type of system may be reduced by as much as 24%, when compared with a more conventional house.